Photography for the 21st century - Miller, Katie (Thomson/Delmar Learning, 2007)
This pioneering book bridges the gap between traditional and digital camera and darkroom techniques, easing the transition from one system to the other while developing an understanding of the scope and importance of the evolution. Photography is investigated as a visual art throughout and cultural references provide a solid understanding of the power and significance of the medium. Readers learn not only how to make photographs-but also how to evaluate their photographs from both technical and aesthetic viewpoints